Արևմտահայ մանկապատանեկան գրականության պատմության ուրվագիծ - Լյուդվիգ Կարապետյան (ՀՀ ԳԱԱ հրատ.)
Западно-армянская детско-юношеская литература является неотъемлемой частью армянской детско-юношеской литературы. Она развивалась в двух взаимопереплетающихся направлениях: исконно детской литературы и вовлеченных в орбиту детско- юношеской литературы прозаических и стихотворных сочинений. Western Armenian literature for children and youth is the inseparable part of Armenian literature for children and youth. It developed in two joint ways: mere children’s works, and poetic and prose works in the frame of literature for children and youth.
Keywords: Literature; Language and Literature